2012
DOI: 10.1155/2012/530128
|View full text |Cite
|
Sign up to set email alerts
|

Cystoid Macular Edema in Acute Presentation of Central Retinal Artery Occlusion

Abstract: A seventy-six-year-old lady with poor vision of the left eye due to previous retinal detachment presented with acute visual loss of her right eye secondary to central retinal artery occlusion. Clinical examination showed a pale right optic disc, macular edema, and a cherry red spot. Optical coherence tomography done four hours after onset showed right acute cystoid macular edema and diffuse inner retinal thickening. Subsequent treatment with intravenous carbonic anhydrase inhibitor resulted in some visual impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…[ 2 3 ] Cases of cystoid macular edema (CME) with a cherry-red spot in acute CRAO without impaired choroidal circulation have also been reported in elderly patients. [ 4 ] In non-arteritic CRAO, the initial presenting vision could be NLP in 7% of the eyes without impaired choroidal circulation. [ 5 ] CRAO causes acute ischemic insult to the inner retinal layers, resulting in diffuse posterior pole intraretinal edema.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 ] Cases of cystoid macular edema (CME) with a cherry-red spot in acute CRAO without impaired choroidal circulation have also been reported in elderly patients. [ 4 ] In non-arteritic CRAO, the initial presenting vision could be NLP in 7% of the eyes without impaired choroidal circulation. [ 5 ] CRAO causes acute ischemic insult to the inner retinal layers, resulting in diffuse posterior pole intraretinal edema.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, macular changes including small cystoids were detected in subacute-stage RAO. Such macular findings are uncommon but have been described in earlier case reports [ 16 , 17 ]. Cystoid macular edema, which is extracellular arising between the inner nuclear and outer plexiform layer, resulting in a “flower petal” appearance, can be seen in acute phase of RAO.…”
Section: Discussionmentioning
confidence: 61%
“…Cystoid macular edema, which is extracellular arising between the inner nuclear and outer plexiform layer, resulting in a “flower petal” appearance, can be seen in acute phase of RAO. Ng WY et al described that the outer retinal layer is involved as well in CRAO [ 16 ]. The pathomechanism is unclear; however, the occurrence of cystoid macular edema means that CRAO does not only affect the inner retina but the outer retinal layer and outer blood-retinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In our analysis, however, 19% of the eyes had cystic fluid accumulation within the ONL. Ng et al 22 described a case of CRAO in an elderly female in which cystoid edema was noted in the ONL on OCT during the acute phase. More recently, Estawro et al 23 reported on two cases with CRAO that developed IRF, one during the acute phase in which the fluid localized to the ONL, and the other during the chronic phase in which fluid localized mainly to the INL.…”
Section: Discussionmentioning
confidence: 99%